2017
DOI: 10.4103/0973-1482.199448
|View full text |Cite
|
Sign up to set email alerts
|

Dual association of serum interleukin-10 levels with colorectal cancer

Abstract: Our results demonstrated a dual association of serum IL-10 levels in the initiation and progression of CRC. While lower IL-10 levels were associated with higher risk of the disease, its higher levels were associated with a poorer prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Local values of cytokines in liquid fraction of feces have shown predomination of anti-inflammatory cytokines TGF- β and IL-10 in patients with severe stadium of CRC (TNM stages III and IV, poor histological differentiation) as well as lower level of proinflammatory IL-1 β in patients with a more progressive disease (presence of metastasis in the liver, lung, and peritoneal carcinomatosis; Figures 1 , 2 , and 3 ). These results are in line with our and other previous studies claiming that serum levels of IL-10 and TGF- β were increased in patients with CRC in comparison to healthy controls and that CRC patients with worse prognosis had increased systemic concentration of IL-10 compared to patients with better prognosis [ 11 , 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…Local values of cytokines in liquid fraction of feces have shown predomination of anti-inflammatory cytokines TGF- β and IL-10 in patients with severe stadium of CRC (TNM stages III and IV, poor histological differentiation) as well as lower level of proinflammatory IL-1 β in patients with a more progressive disease (presence of metastasis in the liver, lung, and peritoneal carcinomatosis; Figures 1 , 2 , and 3 ). These results are in line with our and other previous studies claiming that serum levels of IL-10 and TGF- β were increased in patients with CRC in comparison to healthy controls and that CRC patients with worse prognosis had increased systemic concentration of IL-10 compared to patients with better prognosis [ 11 , 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…These observations are in line with studies showing elevated levels of these specific cytokines upon tumor progression. In humans, IL-10 serum levels increase over time during CRC progression, correlating with poor prognosis [ 39 , 40 , 41 , 42 ], while high levels of ARG-1 were associated with stage III–IV CRC tumors and lymph node metastasis [ 43 ]. Conversely, the protective roles of IL-12 and NOS2 have also been documented.…”
Section: Discussionmentioning
confidence: 99%
“…Increased CXCL10 and IL-6 levels in patient blood have been associated with advanced CRC stage and IL-6 has been suggested as an independent adverse prognostic marker of survival [ 32 , 36 ]. Additionally, an increased pre-operative serum IL-10 level correlates with poor survival in CRC patients [ 37 , 38 ]. It has been reported that during intestinal inflammation macrophage produced IL-23 induce the production of the pro-inflammatory cytokines IL-6 and IL-17.…”
Section: Discussionmentioning
confidence: 99%